2014
DOI: 10.1080/00986445.2013.806311
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hg(ii) Removal From Aqueous Solution Using Lignocellulosic Coconut Fiber Biosorbents: Equilibrium and Kinetic Evaluation

Abstract: Lignocellulosic coconut wastes such as pith and fiber, which are abundantly available and cheap, have the potential of being used as low-cost biosorbents for heavy metal ion removal. In this study, pristine (CF-Pristine) and NaOH-treated (CF-NaOH) coconut fibers were used as a biosorbent for Hg(II) removal from an aqueous solution. The coconut fiber biosorbent (CFB) was characterized by scanning electron microscopy (SEM) and Fourier transform-infrared (FTIR) spectroscopy. The Hg(II) sorption capacities obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The Hg° is generally emitted to the environment from several anthropogenic sources, such as coal-fired power plants, municipal incinerators and wellhead natural gas processing (Padak et al, 2006;Reddy et al, 2014;Skodras et al, 2008). The research direction has been therefore towards the use of cheap adsorbent precusors, such as agriculture wastes (Hsi et al, 2011;Johari et al, 2014b;Saman et al, 2014;Song et al, 2013aSong et al, , 2013bTan et al, 2011Tan et al, , 2012. However, the search for even better and low-cost adsorbents has still been gaining considerable interests owing to the existing adsorbents being too costly to be used as pollution control strategies in many industrial processes.…”
Section: Introductionmentioning
confidence: 99%
“…The Hg° is generally emitted to the environment from several anthropogenic sources, such as coal-fired power plants, municipal incinerators and wellhead natural gas processing (Padak et al, 2006;Reddy et al, 2014;Skodras et al, 2008). The research direction has been therefore towards the use of cheap adsorbent precusors, such as agriculture wastes (Hsi et al, 2011;Johari et al, 2014b;Saman et al, 2014;Song et al, 2013aSong et al, , 2013bTan et al, 2011Tan et al, , 2012. However, the search for even better and low-cost adsorbents has still been gaining considerable interests owing to the existing adsorbents being too costly to be used as pollution control strategies in many industrial processes.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study was conducted by Saman et al where coconut fiber was also utilized, but for adsorption of Ag(I) [107]. Unlike Johari et al [127], study by Saman et al shows that NaOH-treatment enhance Ag(I) removal as its adsorption capacity is higher compared to its pristine form [107]. According to Saman et al, the enhancement in Ag(I) adsorption is attributed to the increase in surface roughness and changes in chemical characteristics of the adsorbents.…”
Section: Coconut Fibermentioning
confidence: 83%
“…Johari et al have conducted an extensive research and provided enough data on utilization of coconut fiber as adsorbent for heavy metal removal. In their study, Johari et al conducted a Hg(II) adsorption and compared the adsorbents' removal capabilities in their pristine and NaOH-treated form [127]. The studies found out NaOH treatment produced an adsorbent with rougher surface and pores that are larger and clearer compared to its pristine form.…”
Section: Coconut Fibermentioning
confidence: 99%
“…Good adsorbents have specific properties such as large pores, availability of oxygen, hydrogen content and Hydroxyl group [21]. The FT-IR was carried using the KBr disk method [25].…”
Section: Ftir Analysis Of Adsorbentsmentioning
confidence: 99%